Paris is burning: Intersectionality in 90s Queer Cinema. - Brew, Tara (Film Matters, 2019)
The overlap of marginalised race and sexuality is highlighted in the 1990 documentary "Paris is burning" which depicts the life of New York's black and Latino drag queens. The author offers an analysis of the social circumstances that gave birth to this culture which originated in 1980s Harlem.
Num Pages: 7-18
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Queer Korean Cinema, National Others, and Making of Queer Space in Stateless Things - Kim, Ungsan (Journal of Japanese & Korean Cinema, 2017)
Analyses the narrative and formal elements of Kim Kyung-mook's "Stateless things" (2011) to argue how it critiques South Korea’s ethnocentrism and homophobic social structures by delineating a queer use of space. Gives recent examples of homoeroticism in commercial and independent South Korean cinema. Argues that Kim's film expand the definition of queer Korean cinema by deconstructing and reconstructing the heteronormative, progress-driven cityscape of Seoul.
Num Pages: 61-79
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Identités diasporiques; _Nettoyé

‘Shanghai is burning’: Extravaganza, Transgender Representation and Transnational Cinema - Bao, Hongwei (Global Media and China, 2018)
This article offers a critical analysis of Matthew Baren’s 2018 film Extravaganza, a documentary about drag scenes in Shanghai. By focusing on some drag performers represented in this film, in tandem with an examination of the social and industry contexts of the film, as well as my interviews with the filmmaker and performers, I problematise the gender identity of the performers and the national identity of the film. Drawing on Deleuze and Guattari’s notion of ‘becoming’ and Song Hwee Lim’s discussion of ‘trans’, I propose to think about certain modes of transnational production with the critical concept of ‘becoming trans’. ‘Becoming trans’ offers a productive way of conceptualising new modes of ‘minor’ transnational cinematic connections in a globalised world without having to resort to identity politics.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Queer Times, Black Futures - Kara Keeling (New York University Press, 2019)
Finalist, 2019 Lambda Literary Award in LGBTQ StudiesA profound intellectual engagement with Afrofuturism and the philosophical questions of space and time Queer Times, Black Futures considers the promises and pitfalls of imagination, technology, futurity, and liberation as they have persisted in and through racial capitalism. Kara Keeling explores how the speculative fictions of cinema, music, and literature that center black existence provide scenarios wherein we might imagine alternative worlds, queer and otherwise. In doing so, Keeling offers a sustained meditation on contemporary investments in futurity, speculation, and technology, paying particular attention to their significance to queer and black freedom.Keeling reads selected works, such as Sun Ra's 1972 film Space is the Place and the 2005 film The Aggressives, to juxtapose the Afrofuturist tradition of speculative imagination with the similar “speculations” of corporate and financial institutions. In connecting a queer, cinematic reordering of time with the new possibilities technology offers, Keeling thinks with and through a vibrant conception of the imagination as a gateway to queer times and black futures, and the previously unimagined spaces that they can conjure.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 5-Identités diasporiques; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."–Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

A Few of My Favourite Things: The Feiticeiro/a as Foundation for ‘Pervert’ Characterisation - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A non-foundationalist construct for the Feiticeiro/a character that assumes neither an essentialist nature nor a determinist set of activities is possible. This does not prescribe a ‘type’ of ‘pervert’ character, but instead delineates an epistemic framing for a Feiticeiro/a character. This chapter explores an etymologically based semiotic approach to character construction that accounts for a Derridean view that language is constituted by binary reciprocal delimitations and for a view of sex as a dereified expression of materialised instances of engagement by sexual subjects, in terms of which sexuality is rendered as an opened-outward and connected function. The chapter further deals with an approach based in an empathic engagement between audiences and Feiticeiro/a characters, which is apposite for audiences identifying with but not necessarily liking characters. The chapter closes the volume’s argument around how transgressive, sexually focused Feiticeiro/a characters might productively be constructed in terms other than of essences and determinist actions, but in terms of ‘meaning’ found in the points of connection between heterogeneous bodily surfaces.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Anthropologically Present ‘Perverts’: Re-instating the Feitiço as the Feiticeiro/a - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A post-humanist lens is useful as a starting-point to remedy the absenting and invisibilising effects of sexological epistemologies for the purposes of conceiving a constitution of ‘pervert’ filmic characters, since certain strains of existential thinking have a meta-theoretical pliancy that is useful for reflecting the non-binary character of complex people beyond simple identity categories, across a range of types and styles of filmic products. If matched with a semiological approach such as that espoused by Barthes, it thereby becomes possible to manipulate signs in the form of character constructions to represent people as more than the sum of their parts and to contain deeper significations that are built into the fabric of their construction. This requires a deeper understanding of the semiotic notion of ‘semes’ as the foundation for character construction. To this end, this chapter explores how sexual ‘perversion’ as reflected in notion of the ‘feitiço’ might serve as a foundation for a new episteme for ‘perverse’ characters, as the Feiticeiro/a as ‘sorcerer/sorceress’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

All About Almodóvar’s Men - Rey, Juan; Uceda Pérez, Francisco (Peter Lang Inc., International Academic Publishers, 2017)
Pedro Almodóvar is an internationally acclaimed Spanish director. The national and international fascination over Almodóvar's cinema lies in his ability to reflect the problems of contemporary society, his lucidity in combining the urban and the rural, his ability to express the frustrations of modern man, as well as his freshness and spontaneity. Although the vast majority of studies on this Spanish director have focused on women and the gay world, his films are crowded with many types and archetypes of heterosexual men. This groundbreaking edited volume studies the men in the cinema of Almodóvar from a broad yet comprehensive and complementary perspective. Each chapter of All About Almodóvar's Men methodically dissects these male characters—their misery and their greatness, their frustrations and their desires—offering a kaleidoscopic view of man that goes beyond the narrow framework in which many studies have locked the rich cinema of Almodóvar.
Issue: vol. 8
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Beyond Bollywood: the Cultural Politics of South Asian Diasporic Film. - Desai, Jigna (Taylor & Francis, 2004)
Beyond Bollywood is the first comprehensive look at the emergence, development, and significance of contemporary South Asian diasporic cinema. From a feminist and queer perspective, Jigna Desai explores the hybrid cinema of the 'Brown Atlantic' through a close look at films in English from and about South Asian diasporas in the United States, Canada, and Britain, including such popular films as My Beautiful Laundrette, Fire, Monsoon Wedding, and Bend it Like Beckham.
OCLC: 824549185
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Queer/Palestinian Cinema: A Critical Conversation on Palestinian Queer and Women's Filmmaking - Jankovic, Colleen; Nadia, Awad (Camera Obscura: Feminism, Culture, and Media Studies, 2012)
While expanding critiques of pinkwashing have drawn increasing attention to how queer issues in Israel and the Occupied Palestinian Territories are perniciously mobilized by a network of lobby groups, Brand Israel initiatives, and international gay and lesbian organizations, these critiques often fail to consider how queer Palestinians mobilize and understand themselves. This article reports on an October 2011 panel and film screening at Yale University and the Hagop Kevorkian Center for Near Eastern Studies at New York University. “Queer/Palestinian: Critical Strategies in Palestinian Queer and Women's Filmmaking” uniquely focused on questions of queerness and Palestine through a program of eight new Palestinian visual productions. The program brought together Palestinian film scholars, filmmakers, visual artists, and curators for a discussion of queer and feminist artistic practice in relation to Palestinian strategies for resistance. Together, the “Queer/Palestinian” films suggest the urgency for Palestinian visual artists to persistently generate new means of expressing, embodying, and critiquing visions for Palestinian society. Films such as Victoria Moufawad-Paul's Nus Enssas/ صيصنصن (Canada, 2011) and Raafat Hattab's Hourieh (Palestine, 2011) explore issues ranging from queer diasporic solidarity politics and challenges to out/closeted binaries and to the creative reinscription of nakba narratives. Nadia Awad's Two Adaptations of the Same Novel (US, 2011), Suzy Salamy's 1982/2006 (US, 2006), and Moufawad-Paul's Rejoice, O My Heart / يبلق اي حرفا (Canada, 2011) suggest an irreverent queer strategy by undermining the narrative conventions and visual codes of mainstream news media and popular US and Egyptian cinema. Salamy's video, previously projected through mobile exhibition on city buildings, and Eli Rezik's online “web-movies” Living Alone without Me (Palestine, 2011) and Between Us Two (Palestine, 2011) compelled a panel discussion of alternative means of distribution and exhibition. Finally, Alaa AbuAsad's Masturbate bil beit (Palestine, 2011) rounded out the program with an explicitly erotic and unapologetically political version of the meeting of “queer” and “Palestinian.”
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Europe (corpus analysé); 5-Identités diasporiques; _Nettoyé

New Queer Sinophone Cinema: Local Histories, Transnational Connections - Pecic, Zoran 1981- (Palgrave Macmillan, 2016)
This book looks closely at some of the most significant films within the field of queer Sinophone cinema. Examining queerness in films produced in the PRC, Taiwan and Hong Kong, the book merges the Sinophone with the queer, theorising both concepts as local and global, homebound as well as diasporic.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé